Q-space analysis of the light scattering phase function of particles with any shape - Sorensen, Christopher M.; Heinson, Y. W.; Heinson, W. R.; Maughan, Justin B.; Chakrabarti, Amitabha (My University, 2017)
Q-space analysis is applied to the light scattering phase function of a wide variety of non-spherical and irregularly shaped particles including a great many types of dusts, fractal aggregates, spheroids, irregular spheres, Gaussian random spheres, thickened clusters and nine types of ice crystals. The phase functions were either experimental data or calculations. This analysis method uncovers many specific and quantitative similarities and differences between the scattering by various shapes and also when compared to spheres. From this analysis a general description for scattering by a particle of any shape emerges with specific details assigned to various shapes. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.
Citation: Sorensen, C. M., Heinson, Y. W., Heinson, W. R., Maughan, J. B., & Chakrabarti, A. (2017). Q-space analysis of the light scattering phase function of particles with any shape. Atmosphere, 8(4). doi:10.3390/atmos8040068
Keywords: Irregularly Shaped Particles; Light Scattering; Phase Function; Q-Space Analysis; Solar Absorbers; Spheres